Trusting the psychotherapist, trusting the governmental system and perhaps trusting the neighbor next door: Exploring the institutional nature of trust in psychotherapists and examining different groups of trusters in a large German patient sample - Marie-Theresa Kaufmann; Christoph Kasinger; Ayline Heller; Elmar Brähler; Bernhard Strauß (Clinical Psychology in Europe, 2026)
Background Trust in psychotherapists is considered primarily interpersonal. However, psychotherapists could be viewed as representatives of the (healthcare) system. In this study, we investigated whether trust in psychotherapists is more closely linked to interpersonal or institutional trust. Furthermore, we explored whether people can be distinguished into different trust groups. Method In a German cross-sectional study sample, we identified 1,300 persons (61.7% female; M = 48.46 years; SD = 14.45 years) indicating experiences with psychotherapy (current and/or in the past). Correlation and linear regression analysis were applied to explore connections between interpersonal (SOEP Interpersonal Trust Scale), institutional (ALLBUS Institutional Trust Scale), and trust in psychotherapists (IIV Psychotherapists). Then, hierarchical cluster analysis was used to identify profiles of interpersonal, institutional, and trust in psychotherapists. Group differences of the cluster solution were analyzed for dimensions that are important for trust and psychotherapy such as having experienced trauma. Results Trust in psychotherapists is not solely associated with interpersonal factors but is also modestly associated with institutional trust. Furthermore, a three-cluster solution emerged with different trust profiles: low trusters (30%) with low scores for all trust measures, high trusters (49%) with the highest values, and system trusters (21%) with the highest trust scores in psychotherapists and institutions, but lower interpersonal trust values. The three groups showed different manifestations of e.g., trauma (LEC-5 Personal Experienced Subscale). Conclusion There is an institutional nature of trust in psychotherapists, which should be reflected and included in research and practice. Implications could include the common measurement of trust in psychotherapists in therapy and broadening psychotherapeutic interventions according to trust needs. To this end, new ways of building trust both in psychotherapy and institutions in general should be explored.